Censuring the Teutonic Philosopher? - Hedley, Douglas (Aries, 2018)
This essay examines Henry More’s engagement with Jacob Böhme and compares the sympathetic critique of Böhme with More’s much more negative evaluation of Spinoza. More directs his criticism of Böhme at the similarities between Spinoza and Böhme: their materialism and confusion of God and world. The present essay suggests, however, that the perception of shared Platonism informs More’s more favourable approach to the Silesian. The problem of what “Platonism” means in this context is thus also addressed. Böhme’s writings were valued by More because of a shared metaphysics that rejected both radical dualism and pantheism, and the Platonic theology of the goodness of God and the freedom of man, together with the rejection of predestination. Spinoza, on the other hand, is rejected because of his radical determinism, his denial of any substantial distinction between good and evil, and the transcendent being of the divine.